Communicating at work : Principles and practices for business and the professions - Adler, Ronald B.; Elmhorst, Jeanne Marquardt (New York McGraw Hill, 2005)
Contents: basics of business and professional communication; personal skills; interviewing; working in groups; making effective presentations.
Includes bibliographical references and index
Keywords: Quản trị kinh doanh